Correlation of Serum IL-2 and IFN-γ Levels with Clinical Prognosis of Nasopharyngeal Carcinoma Patients and Analysis of Risk Factors: Serum cytokine levels and prognosis in nasopharyngeal carcinoma - Guo, Siquan; Qin, Feng; Wang, Jiang; Ding, Yongqing; You, Jianqiang; Chao, Changjiang (Journal of Medical Biochemistry, 2023)
Background: To explore the correlation of serum levels of interleukin-2 (IL-2) and interferon-γ (IFN-γ) with the clinical prognosis of patients with nasopharyngeal carcinoma (NPC) and analyze the risk factors.Methods: The clinical data of 195 NPC patients admitted to our hospital from October 2020 to October 2022 were selected for retrospective study. The patients who obtained 0 point were in good prognosis group (group g), while those who obtained 1-2 points were in poor prognosis group (group p) based on Glasgow score. The levels of serum IL-2 and IFN-γ were compared between the two groups, and the clinical values of serum IL-2 and IFN-γ in the prognosis of patients were analyzed. The clinical parameters of the patients were collected, and the risk factors affecting the prognosis of NPC were analyzed by univariate and multivariate Logistic regression.Results: Among 195 patients, 125 were in the group g and 70 were in the group p. The levels of IL-2 and IFN-γ in the group g were higher than the group p (P
Keywords: IL-2; IFN-γ; nasopharyngeal carcinoma; correlation; risk factors